Plasmodium falciparum intercellular adhesion molecule-1-based cytoadherence-related signaling in human endothelial cells. - Jenkins, N; Wu, Y; Chakravorty, S; Kai, O; Marsh, K; Craig, A (2007)
BACKGROUND: Cytoadherence of Plasmodium falciparum-infected erythrocytes to host endothelium has been associated with pathology in severe malaria, but, despite extensive information on the primary processes involved in the adhesive interactions, the mechanisms underlying disease are poorly understood. METHODS: We compared parasite lines varying in their binding properties to human endothelial cells for their ability to stimulate signaling activity. RESULTS: In human umbilical vein endothelial cells (HUVECs), which rely on adhesion to intercellular adhesion molecule (ICAM)-1 for binding, signaling is related to the avidity of the parasite line for ICAM-1 and can be blocked either through the use of anti-ICAM-1 monoclonal antibodies or HUVECs with altered ICAM-1 binding properties (i.e., ICAM-1(Kilifi)). Human dermal microvascular endothelial cells (HDMECs), which can bind infected erythrocytes via ICAM-1 and CD36, have a more complex pattern of signaling behavior, but this is also dependent on adhesive interactions rather than merely contact between cells. CONCLUSIONS: Signaling via apposition of P. falciparum-infected erythrocytes with host endothelium is dependent, at least in part, on the cytoadherence characteristics of the invading isolate. An understanding of the postadhesive processes produced by cytoadherence may help us to understand the variable pathologies seen in malaria disease.